The role of currency swaps in the domestic banking system and the functioning of the swap market during the crisis - Judit Páles; Zsolt Kuti; Csaba Csávás (Magyar Nemzeti Bank, 2011)
The basic purpose of this study is to didactically demonstrate the factors shaping the currency swap stock of domestic banks prior to the crisis and to provide a descriptive analysis of how the structure and the functioning of the market changed during the crisis. The main conclusions of the study are as follows. In addition to the wide ranging applicability of the transaction, the rise in the currency swap stock of domestic credit institutions is also attributable to macroeconomic factors. The bulk of the exchange rate risk resulting from the high external borrowing requirement and rising external debt was carried by the domestic private sector, while the foreign sector shared a decreasing portion of the risk. The rapid increase in the swap stock was also due to the fact that the synthetic production of foreign currency funds with currency swaps was often more successful than the direct inflow of foreign currency funds. On the basis of the decomposition of the domestic banking system's on-balance sheet foreign currency position, we can state that it increased mainly as a result of items that also increased the balance sheet total. Following the outbreak of the global financial crisis in the autumn of 2008, the conditions for ensuring foreign currency liquidity deteriorated significantly, which had a substantial effect on implied forint yields, and the turnover and structure of the swap market. While the total average turnover of the domestic FX swap market did not drop radically when the crisis was spreading, market liquidity did decline significantly for a few days and access to foreign currency liquidity became limited. The active role assumed by parent banks and shortening maturities contributed to moderating the decline in turnover. Anecdotal information relating to the tightening of counterparty limits vis-à-vis domestic banks is supported by the decline in the number of non-resident counterparties. The crisis also contributed to changes in the structure of the swap stock. The average remaining maturity of the gross stock began to decline directly after the Lehman bankruptcy, at the time of global dollar liquidity problems, followed by a rise starting from early 2009, principally owing to transactions concluded with parent banks. Domestic subsidiary banks managed to increase maturity primarily through cross-currency swap transactions concluded with intra-group counterparties, but non-group counterparties also concluded transactions with longer maturity with domestic banks.
Keywords: E44; F31; F32; F34; 330; FX swap; currency swap; foreign currency based loan; crisis; counterparty limit; margin call; liquidity requirement; Währungsderivat; Finanzkrise; Bankenliquidität; Basler Akkord; Ungarn